2020
DOI: 10.17269/s41997-020-00413-3
|View full text |Cite
|
Sign up to set email alerts
|

Will peer-based interventions improve hepatitis C virus treatment uptake among young people who inject drugs?

Abstract: People who inject drugs (PWID) are disproportionately affected by hepatitis C virus (HCV) and have low rates of direct-acting antiviral (DAA) treatment uptake, despite universal coverage of the medication in most Canadian settings. Investigation into peer-based interventions as a means of improving treatment uptake has yielded promising results in adult PWID populations. In this commentary, we discuss the benefits and considerations of integrating peer-based interventions into HCV care for adolescent and young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…At least, around Spain there are several similar centers with almost comparable resources than can implement this model of care. Pretty similar models are already working in addictions center and mobile clinics (Denmark) [ 34 , 35 ], where peers [ 36 ] help people to join these centers to take screening tests and to enroll harm reduction program and treatment facilities in Canada [ 37 ] and Mexico [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…At least, around Spain there are several similar centers with almost comparable resources than can implement this model of care. Pretty similar models are already working in addictions center and mobile clinics (Denmark) [ 34 , 35 ], where peers [ 36 ] help people to join these centers to take screening tests and to enroll harm reduction program and treatment facilities in Canada [ 37 ] and Mexico [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that young people who inject drugs report significant knowledge gaps related to hepatitis C transmission and minimise the risks associated with sharing injecting equipment, demonstrating a need for harm reduction initiatives to effectively reach young people when they first start injecting drugs [32,33]. For example, peer-based interventions have been argued to empower young people who inject drugs to share their experiences and knowledge and have positive outcomes in terms of delivering health promotion messaging [34]. There are therefore a range of personal, social and structural factors which influence equipment sharing among people who inject drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, peer mentors have found success in clarifying misinformation concerning HCV treatment, such as concerns about interactions with ART for HIV (Jost et al, 2019). Peer-based interactions have been shown to improve treatment uptake and overall health promotion through increased sharing of experiences and knowledge (Jacob et al, 2021). A critical component of this approach would be ensuring support to peer mentors including educational resources (e.g., Project ECHO [Waridibo et al] and the ConnQuER HepC application [ConnQuER HEP C Application, 2019]) and specialized training which has been effective for PWH (Burns et al, 2021; Wambua et al, 2019).…”
Section: Discussionmentioning
confidence: 99%